2018
DOI: 10.1016/j.autrev.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and systemic lupus erythematosus - The hype and the hope

Abstract: Over the past 20years, much has been written about the potential role of vitamin D in on adverse health outcomes. In recent years, evidence has accumulated regarding the effect of vitamin D on the immune system, and its different cells. Some studies have noted lower vitamin D concentrations in patients with SLE. These epidemiological data still not answer the question: is vitamin D deficiency the cause or the effect? To answer this, we will discuss the association between vitamin D deficiency and SLE and revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 57 publications
1
46
0
2
Order By: Relevance
“…Different supplementation regimens also demonstrated improvement in inflammatory markers, disease activity indices, decrease in T-helpers types 1 and 17 [44]. However, despite the different papers, reporting beneficial effect from VD, a recent study demonstrated increase of SLE activity after exposing patients to UV radiation, despite improvement in VD status [45]. Thus, the SLE-VD correlation still remains to be clarified.…”
Section: Vd and Autoimmunity/inflammationmentioning
confidence: 97%
“…Different supplementation regimens also demonstrated improvement in inflammatory markers, disease activity indices, decrease in T-helpers types 1 and 17 [44]. However, despite the different papers, reporting beneficial effect from VD, a recent study demonstrated increase of SLE activity after exposing patients to UV radiation, despite improvement in VD status [45]. Thus, the SLE-VD correlation still remains to be clarified.…”
Section: Vd and Autoimmunity/inflammationmentioning
confidence: 97%
“…Плейотропна дія вітаміну була відзначена багатьма спостереженнями, що свідчить про існуючий зв'язок між низькою концентрацією 25(OH)D і підвищеним ризиком онкологічних (зокрема, раку кишечника, молочних залоз, яєчників, простати, підшлункової залози, шкіри, нирок, мозку, численних різновидів мієломи й лейкемії) [74][75][76][77][78], імунологічних захворювань (розсіяного склерозу [79][80][81][82], астми [83,84], неспецифічного запального захворювання кишечника [85,86] й системного червоного вовчака [87,88]), автоімунних ендокринних порушень (діабет І типу [89,90], хвороба Аддісона [91,92], хвороба Хашімото [93,94], Базедова хвороба, хвороба Грейвса [95,96] й автоімунні поліендокринні синдроми [97]), імунодефіциту й рецидивуючих інфекцій [98] (зокрема, туберкульозу й грипу), компонентів метаболічного синдрому (артеріальної гіпертензії, серцево-судинних хвороб, атеросклерозу, ішемічної хвороби серця, діабету І типу, ожиріння) [99][100][101][102][103][104][105], психіатричних порушень (депресія [106], шизофренія [107,108]), нейродегенеративних хвороб (деменція [109][110][111], хвороба Альцгеймера [112,113], порушення когнітивної функції [109,110,…”
Section: кальціємічний ефект вітаміну Dunclassified
“…Aspekt działania plejotropowego witaminy D testowano w licznych badaniach obserwacyjnych, które sugerują istnienie związku między niskim stężeniem 25(OH)D w surowicy a zwiększonym ryzykiem nowotworów (między innymi okrężnicy, piersi, jajnika, prostaty, trzustki, skóry, guzów mózgu, nerek, szpiczaka mnogiego, białaczki) [73][74][75][76][77], chorób o podłożu immunologicznym (stwardnienie rozsiane [78][79][80][81], astma oskrzelowa [82,83], nieswoiste choroby zapalne jelit [84,85], toczeń rumieniowaty układowy [86,87], w tym autoimmunizacyjnych zaburzeń endokrynnych (cukrzyca typu 1 [88,89], choroba Addisona [90,91], choroba Hashimoto [92,93], choroba Gravesa-Basedowa [94,95], autoimmunologiczne zespoły niedoczynności wielogruczołowej [96]), zaburzeń odporności i nawracających infekcji [97] (między innymi gruźlicy i grypy), chorób cywilizacyjnych (w tym nadciśnienia tętniczego i chorób układu sercowo-naczyniowego, miażdżycy, choroby niedokrwiennej serca, cukrzycy typu 2, otyłości) [98][99][100][101][102][103][104], a także zaburzeń psychiatrycznych (depresji [105], schizofrenii [106,107]) oraz chorób neurodegeneracyjnych (demencji 108-110], choroby Alzheimera [111,112], obniżenia funkcji poznawczych [108,…”
Section: Działanie Plejotropowe Witaminy Dunclassified